1992
DOI: 10.1007/bf01710687
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas vesicularis bacteraemia

Abstract: A case of repeated episodes of Pseudomonas vesicularis bacteraemia, in a 54-year-old woman with a past history including systemic lupus erythematosus and chronic active autoimmune hepatitis is reported. She was treated with tobramycin and ceftazidime but bacteraemia persisted until surgical resection of the infected tissue was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Isolated from both environmental and clinical specimens, 2,3 B. vesicularis is an aerobic, nonsporulating and glucose non-fermenting Gram-negative bacillus (GNB) with distinct nutritional requirements and biochemical characteristics. 4,5 The organism produces slow-growing and yellowpigmented colonies on blood and chocolate agar. 4e7 Although some authors have observed that the organism does not grow in MacConkey's agar, 4 longer incubation might reveal macroscopically-visible growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated from both environmental and clinical specimens, 2,3 B. vesicularis is an aerobic, nonsporulating and glucose non-fermenting Gram-negative bacillus (GNB) with distinct nutritional requirements and biochemical characteristics. 4,5 The organism produces slow-growing and yellowpigmented colonies on blood and chocolate agar. 4e7 Although some authors have observed that the organism does not grow in MacConkey's agar, 4 longer incubation might reveal macroscopically-visible growth.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The organism produces slow-growing and yellowpigmented colonies on blood and chocolate agar. 4e7 Although some authors have observed that the organism does not grow in MacConkey's agar, 4 longer incubation might reveal macroscopically-visible growth. 6 Few reports of invasive infections caused by B. vesicularis exist in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…4 Brevundimonas species are aerobic, non-sporulating, slender, motile, and nonfermenting Gram-negative bacilli. 3,5,6 They are environmental organisms and they have a distribution all around the world. 3,5 These microorganisms have been isolated from water, soil, plants, and various clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 They are environmental organisms and they have a distribution all around the world. 3,5 These microorganisms have been isolated from water, soil, plants, and various clinical specimens. However, they are also rarely isolated from the environment and from clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation